Evaluation of the Brazilian global atmospheric model in the simulation of the water budget components in the amazon basin - Moura, Rildo Gonçalves de; Correia, Francis Wagner Silva; Veiga, José Augusto Paixão; Capistrano, Vinícius Buscioli; Kubota, Paulo Yoshio (Revista Brasileira de Meteorologia, 2021)
This study evaluated the performance of the Brazilian Global Atmospheric Model (BAM) in the representation of water balance components in the Amazon basin for the present climate (1979-2015). The BAM model reproduces the spacetemporal variation of the water balance components in the Amazon basin, despite the deficiency in correctly positioning the maximum precipitation and moisture convergence over the region. BAM underestimated precipitation (8,8%) and runoff (36,8%), and overestimated evapotranspiration (5,3%). Moisture sink behavior was well represented by BAM, since precipitation is always greater than evapotranspiration (P > E) in the Amazon basin. The non-closure of the water budget (52,6%) in the basin shows the limitation of BAM physical parameters in the representation of convection (precipitation) and moisture convergence, proving the need for better adjustments. Overall, despite underestimating rainfall, BAM adequately simulated annual and seasonal rainfall. The evapotranspiration was overestimated, especially in the rainy season, but was underestimated in the dry season. The results showed that BAM needs adjustments and calibration in the representation of surface processes, since it presented difficulty in simulating the seasonal variation of evapotranspiration. Systematic errors found in water balance components are of great importance in determining the degree of confidence for present climate simulations and future projections. © 2021, Sociedade Brasileira de Meteorologia. All rights reserved.
[Avaliação do Brazilian global atmospheric model na simulação dos componentes do balanço de água na bacia amazônica]
Keywords: Amazon basin; Brazilian global atmospheric model (BAM); Water balance